Dietary behavior of video game players and esports players in Germany: a cross-sectional study - Markus Soffner; Peter Bickmann; Chuck Tholl; Ingo Froböse (BMC, 2023)
Abstract Background Video gaming and competitive gaming (esports) are gaining more and more recognition in society as well as in research. Increasingly, health-related topics are the focus of research on video game and esports players. Although video gaming is often associated with energy drinks and fast food, no studies have yet examined the players' dietary behavior. Therefore, the aim of this cross-sectional study is to investigate the dietary behavior and additional health-related data of video game players and esports players in Germany. Methods Between July and October 2020, 817 participants (87.1% male; 24.2 ± 6.9 years), divided into video game players and esports players, were surveyed via an online questionnaire about their dietary, health, and gaming behaviors. Descriptive statistics were performed on all questions. To investigate statistically significant differences between video game players and esports players, the Mann-Whitney-U-Test and Kruskall-Wallis-Test were used. Partial Spearman correlations were used to examine possible associations between dietary behavior, health status, well-being, and video game playing time. Results Water was the primary source of fluid intake for the players (10.9 ± 7.0 l/week). The average weekly consumption of energy drinks was 0.4 ± 0.9 L. Energy drinks (rho = 0.14; p < 0.01) as well as soft drinks (rho = 0.14; p < 0.01) are positively correlated with the video game playing time. Participants ate 7.5 ± 10.4 servings of fast food per month, which has a positive association with video game playing time (rho = 0.13; p < 0.01). In contrast, vegetables (1.7 ± 1.6 servings/day) and fruits (0.9 ± 1.0 servings/day) are eaten almost daily. Conclusion In this survey, the dietary behavior of video game players and esports players is similar to that of the German general population. Nevertheless, there is a need for improvement. Especially energy drinks, which are already documented to have adverse health effects, should be limited. In addition, the consumption of fast food and meat should also be reduced, and healthier foods such as fruits and vegetables should be increased instead. Early education and support regarding the associated risks with unhealthy foods is important within the target group.